International Law and International Relations: Norm and reality or viceversa - Fred Grunfeld (Amsterdam Law Forum, 2011)
The fields of Public International Law (PIL) and International Relations (IR) share the same research area: international politics.This article focuses on the differences between social scientists (especially political scientists studying International Relations) and legal researchers (specifically in the fields of Public International Law and human rights) in terms of research methods. The focus on methodology will highlight the difference between the researchers of Public International Law on the one hand, and International Relations on the other.